2016
DOI: 10.21037/tcr.2016.08.40
|View full text |Cite
|
Sign up to set email alerts
|

TP53 mutations in epithelial ovarian cancer

Abstract: Genomic sequencing analyses of a variety of human cancers have revealed that massive mutations of cancer-relevant genes are the major alterations in cancerous cells, and their mutation frequencies or rates are highly associated with the development, progression, metastasis, and drug resistance of cancers as well as their clinical outcomes and prognosis. One predominant genetic alternation in human epithelial ovarian cancer (EOC) is the mutation of TP53 that encodes the tumor suppressor p53 protein. This essay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 108 publications
10
72
0
Order By: Relevance
“…TP53 mutations were the most frequently co-occurring genomic alterations among ascites ctDNA, preoperative plasma ctDNA, and tumor DNA from EOC patients. Many studies have shown that TP53 mutations are significantly associated with EOCs because TP53 mutations are identified in 97% of the most aggressive high-grade serous ovarian carcinomas, which account for more than two-thirds of all ovarian cancers [19]. We also found that NTRK1, PIK3CA, and MYC mutations co-occurred among ascites ctDNA, preoperative plasma ctDNA, and tumor DNA from our EOC patients.…”
Section: Discussionsupporting
confidence: 58%
“…TP53 mutations were the most frequently co-occurring genomic alterations among ascites ctDNA, preoperative plasma ctDNA, and tumor DNA from EOC patients. Many studies have shown that TP53 mutations are significantly associated with EOCs because TP53 mutations are identified in 97% of the most aggressive high-grade serous ovarian carcinomas, which account for more than two-thirds of all ovarian cancers [19]. We also found that NTRK1, PIK3CA, and MYC mutations co-occurred among ascites ctDNA, preoperative plasma ctDNA, and tumor DNA from our EOC patients.…”
Section: Discussionsupporting
confidence: 58%
“…As it is unknown whether the ability of detached HGSC cells to colonize serous membranes might be linked to newly acquired genetic alterations, we per- mutations were found in 9 of 10 patients [56]. Likewise, ADAMTS8 was altered by SNVs in the majority of patients (6/10; in 3 cases simultaneously at 2 different sites), while 8 other loci were affected in a smaller subset of patients (1-5 out of 10).…”
Section: Genetic Alterations In Hgsc Metastasis and Spheroidsmentioning
confidence: 94%
“…To understand the therapeutic potential of a protein target, there must be an appreciation of the underlying genetic abnormalities specific to the cancer type. The TP53 gene (tumor suppressor p53) is the most commonly mutated gene in all ovarian cancers and is especially a prognostic marker of HGSOC (80). In contrast, CCOC typically has a wild type TP53 and mutations in the tumor suppressor ARID1A (81).…”
Section: Targeting Apkcs In Ccocmentioning
confidence: 99%